Internalizing Civic Values in the Digital Era: The Role of Artificial Intelligence in Civics Education (PPKn) - Nurlaili Arifah; Yasir Marzuqi (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Background: The growing presence of artificial intelligence (AI) in education is beginning to reshape how civic values are internalized in Pancasila and Civic Education (PPKn). This study examines the challenges and opportunities of internalizing civic values in the digital era, describes the role of AI in PPKn instruction, and identifies how AI can be used to strengthen students' civic character. Method: A descriptive qualitative case study was conducted at SMK Muhammadiyah 3 Yogyakarta, involving a PPKn teacher and tenth-grade students selected through purposive sampling. Data were collected through in-depth interviews, classroom observation, and documentation, and were analyzed using the interactive model of Miles and Huberman. Result anda Discussions: The findings show that internalizing civic values in the digital era involves several challenges, including a decline in students' social ethics, a growing dependence on AI, and the absence of clear institutional guidelines for classroom AI use. At the same time, digital technology creates opportunities for creativity, more interactive learning, and stronger digital literacy. Teachers and students use AI as a learning resource, a medium for discussion, and a support for project-based activities that help students understand and practice civic values such as honesty, responsibility, tolerance, mutual cooperation (gotong royong), and digital ethics. The results further indicate that AI use is most effective when combined with collaborative and contextual learning under consistent teacher guidance. Conclusion: The study concludes that AI can support the internalization of civic values when it is used purposefully, ethically, and in line with the goals of PPKn instruction.